2013
DOI: 10.1049/iet-epa.2012.0319
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Design and control of a high‐speed switched reluctance machine with conical magnetic bearings for aircraft application

Abstract: The following article published in IET Electric Power Applications, Ding, Wen; Liu, Ling: Lou, Jianyong: 'Design and control of a high‐speed switched reluctance machine with conical magnetic bearings for aircraft application', IET IET Electric Power Applications, 2013, Volume 7, Issue 3, doi: 10.1049/iet‐epa.2012.0319 has been retracted. Following a rigorous and considered review of this content, this paper has been found to be in violation of the IET’s Policy in Relation to Plagiarism, Infringement of Copyrig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In this category, there are four general types of SRMs. The initial classification is performed according to motion type offered by the machine: the rotary [11, 12, 15–19], linear [20–22] and rotary‐linear [10, 14, 23–25]. The rotary machines are classified into four general types of ‘axial flux’, ‘radial flux’, ‘diagonal flux’ and a combination of all called ‘multi‐air‐gap’ according to position of the air‐gap magnetic flux relative to the machine's rotation axis.…”
Section: Introductionmentioning
confidence: 99%
“…In this category, there are four general types of SRMs. The initial classification is performed according to motion type offered by the machine: the rotary [11, 12, 15–19], linear [20–22] and rotary‐linear [10, 14, 23–25]. The rotary machines are classified into four general types of ‘axial flux’, ‘radial flux’, ‘diagonal flux’ and a combination of all called ‘multi‐air‐gap’ according to position of the air‐gap magnetic flux relative to the machine's rotation axis.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic bearing has the advantages such as low consumption, longevity, and low maintenance requirement, making it suitable for the special occasions such as the high‐speed motor, vacuum facilities super clean sterile room, the machining process and superconductor [1–4]. The power amplifier is the key component of a magnetic bearing system, which is used to amplify the control signals of the coil current needed to generate the magnetic force.…”
Section: Introductionmentioning
confidence: 99%
“…The switched reluctance machine (SRM) is anticipated to be used in a growing number of applications due to its inherent simple construction, low inertia, high torque‐weight ratio, easy speed control, and strong fault tolerance. Plenty of studies about the controller, driver, and optimisation of the SRM have been reported [1–6]. Before these developments were employed in reality, off‐line simulation was always employed to verify the performance of the control system.…”
Section: Introductionmentioning
confidence: 99%